Analysis of External Factors on the Accuracy of Object Detection by LidarSensor: Article - Abdrakhmanov, Arsen; Ilipbayeva, Lyazzat (Journal of Emerging Technologies and Computing, 2025)
The research examines the role of external factors—ambient illumination, surface reflectivity, and laser incidence angle—on the accuracy as well as stability of distance measurements with the compact LiDAR sensor TF-Luna. A MATLAB model for simulation was created to assess how each of these parameters influence the accuracy of the output of the sensor. The model includes Lambert’s cosine law, variable reflectivity values between 0.1 and 0.9, and up to 70,000 lux illumination levels. The simulation outputs show that high values of brightness, low reflective surfaces, and high angles of incidence dramatically reduce the accuracy of measurement, raising error bounds as well as the likelihood of failure. The evidence supports critical reliance of TF-Luna’s operation on environmental factors. Recommendations have been proposed for alleviating such effects when the sensor is employed for mobile robotics and remote sensing purposes.